2019
DOI: 10.1007/s10569-019-9897-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-averaged regularized formulations as an alternative to semi-analytical orbit propagation methods

Abstract: This paper is concerned with the comparison of semi-analytical and non-averaged propagation methods for Earth satellite orbits. We analyse the total integration error for semi-analytical methods and propose a novel decomposition into dynamical, model truncation, short-periodic, and numerical error components. The first three are attributable to distinct approximations required by the method of averaging, which fundamentally limit the attainable accuracy. In contrast, numerical error, the only component present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Amato et al [44] showed that special perturbation methods based on regularized formulations can compete and even outperform the semi-analytical methods for the long-term propagations (on the order of decades) of objects orbiting around the Earth. For this kind of applications, the Cowell formulation has never been used because of the required small integration step sizes, which causes strong accumulation of round-off error and long computational time.…”
Section: Work On the Ks And Quaternion Regularization Of The Two-body Problem Equations By Other Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amato et al [44] showed that special perturbation methods based on regularized formulations can compete and even outperform the semi-analytical methods for the long-term propagations (on the order of decades) of objects orbiting around the Earth. For this kind of applications, the Cowell formulation has never been used because of the required small integration step sizes, which causes strong accumulation of round-off error and long computational time.…”
Section: Work On the Ks And Quaternion Regularization Of The Two-body Problem Equations By Other Authorsmentioning
confidence: 99%
“…Stiefel and Scheifele [37] , Bordovitsyna [38] , Bordovitsyna and Avdyushev [39] , Fukushima [40][41] , Pelaez et al [42] , Bau et al [43] , Amato et al [44] , and Bau and Roa [45] demonstrated the results of comparing the numerical solutions to the equations of orbital motion of celestial and cosmic bodies in the KS variables, Euler parameters, and other variables. These results prove the efficiency of the KS variables and Euler parameters in celestial mechanics and astrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…This is a very demanding process in terms of CPU time (the computation of MiSO initial conditions for an individual constellation plane can take a few hours with an Intel Core processor i7-4790@3.6GHz) where the use of a very efficient orbit propagator is paramount. All numerical propagations were performed using the THALASSA orbit propagator [16], [17].…”
Section: Minimum Space Occupancy (Miso) Orbitsmentioning
confidence: 99%
“…Discussions on symplectic integration methods applied to celestial mechanics and astrodynamics can be found in [21,22,23,24]. Formulations tailored for specific problems include the DROMO regularized propagator [25] and its developments [26,27,28]. [29] describes a fast numerical integration technique using a low-fidelity force model for tracking purposes.…”
Section: Introductionmentioning
confidence: 99%